Conventional Control of Loop-Height in Steel Rolling Mill - Abdulrahman, Alaa Muheddin (Sulaimani Journal for Pure and Applied Sciences, 2008)
This paper describes the loop height formation in steel rolling mill, and how to control the height of the loop. Loops are useful in stee0l rolling processes. They improve the quality of the steel production and reduce the chances of tension and/or bending in the production between the successive rolling stands. The driver of the rolling stand is of DC-motor type in which its speed can be controlled. A conventional controller is used to control the height of the loop and to keep the synchronization of the rolling stands. Simulation results reveal how the synchronization is maintained and the height of the loop can be kept constant when any disturbances occur.
Keywords: Loop height; Steel Rolling Mill; Control